HUBUNGAN ANTARA DUKUNGAN IKLIM SEKOLAH, DUKUNGAN IKLIM KELUARGA, PENGARUH TEMAN SEBAYA DENGAN PERUNDUNGAN ANTAR SISWA SEKOLAH MENENGAH PERTAMA : PERAN MEDIASI VARIABEL KESEJAHTERAAN PSIKOLOGIS - Fajar Haryadi; Yeri Sutopo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Bullying remains a serious issue in schools, as indicated by the high number of reported cases by the Indonesian Child Protection Commission (KPAI) and the Indonesian Teachers Federation (FSGI). It is a form of intentional aggression aimed at causing physical, emotional, or social harm. A negative and unsupportive family environment, along with unhealthy peer relationships—especially when individuals feel superior to others—can trigger involvement in bullying behavior. Additionally, a non-conducive school climate can negatively impact students’ psychological well- being. This study aims to examine the direct and indirect effects of school climate support, family climate support, and peer influence on bullying behavior among junior high school students, with psychological well-being serving as a mediating variable. It also explores the direct effect of psychological well-being on bullying. A deductive approach was applied, starting from existing theories to develop hypotheses for empirical testing. The research used a quantitative survey method with an ex post facto design, as the data reflect past events without any manipulation of variables. Analytical techniques included regression and path analysis to assess both direct and indirect relationships. Confirmatory Factor Analysis (CFA) up to the second-order level was conducted using LISREL version 8.80, and descriptive statistics were processed using SPSS version 21.Results showed that support from school, family, and peers significantly influences students’ psychological well-being. These three factors were proven to be strong predictors of mental resilience. It is recommended that future studies treat bullying as an independent variable, as empirical and theoretical evidence suggests it functions better as a risk factor affecting students’ mental health.